(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The Internet is extremely important because it is a limitless space where people have access to an infinite amount of information. The Internet is where a large amount of knowledge comes from. Wi-Fi connection using a vending machine can be the cheapest Internet connection because a vending machine is coin-operated. “Coin-operated” means that one only needs to insert a coin on the machine to access the Internet through a Wi-Fi connection. The idea of Piso-net largely influenced the creators of the J2KLC Wi-Fi Vendo machine to establish this kind of business. The word J2KLC came from the acronym of each member of the researchers. The researchers provided an affordable and easy way to have an internet connection to the community and also give profit to possible customers. The business was established to provide convenient Internet connection to the customers and meet the expectation of the target market. The proponents conducted surveyed 70 respondents to know what products and services the customers will avail themselves of in the J2KLC Wi-fi Vendo machine. The researchers studied the product, price, place, and promotion of the product. According to the results of the survey after completing the feasibility study of the proposed business, the researchers concluded that the establishment of the J2KLC Wi-fi Vendo machine is feasible and will be viable based on different studies. The researchers recommended adding additional freebies and extensions for the business to make the business visible and provide products that are of good quality to satisfy the customers. To build a loyal following, the business should plan for expansion.